Oliverio Girondo y la fealdad en poesía - Murillo Chinchilla, Verónica (2016)
The aim of this article is to think about the concepts of ugliness and degradation in three poems by Oliverio Girondo : “Ejecutoria del miasma”, “Testimonial”, and “Hay que compadecerlos”, all belonging to his book Persuasión de los días. In these poems, it is possible to discern more clearly the social, moral, and aesthetic radicalism characterizing Girondo as a vanguardist poet. His worries about the essence of human being and the world, his doubts about our place in this world and the functioning of the gear of existence, are determinant elements in the poetic work of Oliverio Girondo.